2014
DOI: 10.1002/em.21865
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the Saccharomyces cerevisiae efflux pump Tpo1 rescues an Imp2 transcription factor‐deficient mutant from bleomycin toxicity

Abstract: Yeast mutants lacking the transcriptional co-activator Imp2 are hypersensitive to the anticancer drug bleomycin, although the gene targets involved in this process remain elusive. A search for multicopy suppressors that rescue the imp2Δ mutant from bleomycin toxicity revealed the transcriptional activator Yap1, which can turn on many target genes such as transporters involved in regulating drug resistance. We show that YAP1 overexpression stimulated the expression of the TPO1 gene encoding a polyamine efflux p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Certain cell membrane proteins, notably the human high affinity l -carnitine transporter, can modulate the accumulation of and subsequently the sensitivity of tumour cells to bleomycin. It was found that overexpression of the yeast polyamine transporter TPO1 increased resistance to bleomycin [ 160 ]. The yeast TPO1 transporter was previously found to be involved in the efflux of polyamines from the cell [ 161 , 162 ].…”
Section: Cellular Transport Of Bleomycinmentioning
confidence: 99%
“…Certain cell membrane proteins, notably the human high affinity l -carnitine transporter, can modulate the accumulation of and subsequently the sensitivity of tumour cells to bleomycin. It was found that overexpression of the yeast polyamine transporter TPO1 increased resistance to bleomycin [ 160 ]. The yeast TPO1 transporter was previously found to be involved in the efflux of polyamines from the cell [ 161 , 162 ].…”
Section: Cellular Transport Of Bleomycinmentioning
confidence: 99%
“…The single-copy plasmid pSTE5-GFP carrying the entire STE5 gene under its promoter and tagged with GFP was kindly provided by Dr. Peter M. Pryciak (University of Massachusetts medical school, Worcester, MA, USA). The plasmid pSTE5-Myc was constructed by gap repair using pTW438 as the backbone and as previously decsribed 26 . All chemical reagents including rapamycin, methyl methanesulfonate, 4-nitroquinoline-1-oxide, bleomycin and sodium arsenite were purchased from Sigma, St Louis, USA.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, our laboratory has dedicated research efforts to the study of the biological role and regulation of drug/xenobiotic pumps of the major facilitator superfamily (MFS) and the ATP-binding cassette (ABC) superfamily, and the link between their physiological role and the MDR/MXR phenomenon in yeast (Sá-Correia et al 2009). The S. cerevisiae plasma membrane drug:H + antiporter (DHA) Tpo1, a MDR/MXR transporter of the MFS, has been found to mediate tolerance of this yeast species to a high number of cytotoxic compounds including the metal ions cadmium and aluminium (Cabrito et al 2009), the antimalarial drugs quinidine and artesunate (Alenquer et al 2006; do Valle Matta et al 2001), the immunosuppressant mycophenolic acid (Desmoucelles et al 2002), the herbicides 2,4-dichlorophenoxyacetic acid (2,4-D) and barban (Cabrito et al 2009; Teixeira and Sá-Correia 2002), the anticancer agent bleomycin (Berra et al 2014; Hillenmeyer et al 2008), the antifungals nodoconazole and mancozeb (Dias et al 2010; Hillenmeyer et al 2008), the nonsteroidal anti-inflammatory drug diclofenac (Mima et al 2007) and the weak acids acetic, propionic, decanoic and octanoic acids (Borrull et al 2015; Legras et al 2010; Mira et al 2009). The apparent promiscuity of Tpo1 and other yeast MFS-MDR transporters in conferring protection to a wide range of structurally unrelated xenobiotic compounds has been questioning the idea that these transporters contribute to MDR by directly mediating the extrusion of the drugs (Dos Santos et al 2014; Mira et al 2010a; Sá-Correia et al 2009).…”
Section: Introductionmentioning
confidence: 99%